Hmong Cultural Landscape of Eau Claire, Wisconsin. - Moua, Pa Sia Lor (My University, 2009)
This research project is a closer look into the Hmong community in Eau Claire, Wisconsin, to build an understanding of the patterns in which the Hmong population reside and how their cultural practices and daily lives alter and affect the cultural landscape.
Color poster with text, images, and maps (Spring 2009)
Keywords: Hmong Americans--Social life and customs; Hmong Americans--Wisconsin--Eau Claire; Posters; Hmong (Asian people)--Wisconsin--Eau Claire